Penerjemahan Kolokasi pada Buku Bacaan Anak Dwibahasa - Diana Hardiyanti; Riana Eka Budiastuti (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2017)
Collocation is a language phenomenon that shows some words go together to form a fix relationship. Understanding collocation will help the translator to produce a natural text in target language. Children bilingual story books become a solution for those, especially parents, who want to help their children in learning English. Bilingual book in this research is from Indonesian into English. Children story book mostly uses simple sentences. Therefore, the translation is usually use word for word method. The aim of this research were to identified the kinds of collocation found in Children bilingual story books, the method used and the naturalness of the target text. The method of this research was qualitative descriptive. The data for the research is the collocation from word or phrase in Indonesian and its translation in English. The data is taken from Children bilingual story books sold in the regional book store. The collocations of the source text are grouped into adjective +noun, noun + noun, verb + object. The collocations of the source text were compared to the target text to identify the translation method to relate to the naturalness in the target language. The appropriate method of translating the text influences the quality of the translation.